Investigation of bidirectional three-phase four-leg converter with LCL filter - Dobroskok, Nikita A.; Stotckaia, Anastasiia D.; Migranov, Ruslan M.; Lavrinovskiy, Victor S.; Yurievich, Perevalov Yurii; Melnikov, Artem S.; Parmenov, Vyacheslav; Maslennikov, Nazar V. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
A three-phase four-leg bidirectional power converter used as an input stage of an energy storage system using the inductance (L), capacitance (C), and inductance (L) or LCL filter on the grid side is considered. The article provides a variant of the three-phase four-leg bidirectional converter control system implementation based on 3D space vector pulse-width modulation and per-phase voltage control. A brief analysis of the applied control algorithms of the three-phase four-leg bidirectional converter in inverter and rectifier modes is given. A computer model has been built to investigate the operating modes of the converters of the designated class with both balanced and unbalanced load. Studies were carried out by computer modeling methods in order to optimize the parameters of the LCL filter on the grid side with bidirectional energy exchange. Optimal LCL filter parameters and modulation frequencies are determined for the developed converter, providing acceptable quality indicators when operating in bidirectional mode.